Book Review: Sejarah Pertama Alkitab: Dari Eden hingga Kerajaan Daud Berdasarkan Sumber Y: Book Review: The Bible’s First History: From Eden to the Court of David with the Yahwist - Aseng Yulias Samongilailai; Barnabas Ludji (Sekolah Tinggi Teologi Baptis Indonesia, 2021)
This book explains the source of Y by focusing on social, economic, and even political aspects. The description contained in it is not only limited to explaining the source of Y, but has been accompanied by the interpretation of the two authors. In this book, it is explained that the Y source is written with the background of the strong Egypt as one of the superpowers and the Israel kingdom under David's monarchy, here Egypt is the biggest threat. The question is, why Egypt? Aren't there other superpowers in addition to Egypt, such as the Mycenaeans, Hittites, and Assyrians? And is it true that source Y was written at the time David was king of Israel kingdom? This is explained at length in this book. In addition, source Y also has another agenda, namely how to unite the twelve tribes into one nation in a new kingdom under the Davidic dynasty. Why did David have to do this? The initial answer given is because it relates to their existence in the midst of other kingdoms and nations. The way that David tried to convince his people was by bringing up the story of Abraham's calling, especially the affirmation “Israel is a great nation, chosen and blessed. These two agendas are a big framework for understanding this book.